Effects of cold exposure on behavioral and electrophysiological parameters related with hippocampal function in rats - Elmarzouki, Hajar; Aboussaleh, Youssef; Bitiktas, Soner; Suer, Cem; Artis, A. Seda; Dolu, Nazan; Ahami, Ahmed (Frontiers in Cellular Neuroscience, 2014)
Aim: Behavioral and mental changes may occur in people exposed to cold stress by decreasing their work efficiency and their mental capacity while increasing the number of accidents on the job site. The goal of this study was to explore the effect of cold stress in spatial learning performance excitability and long term potentiation. Materials and Methods: Three to four month old rats were randomly divided into four groups to form a control group and a cold stress group for each sex. The groups of cold stressed animals were placed in a cold room (ambient temperature of (4°C) for 2 hours day. Adrenal glands and body weight (g) were recorded in control and stressed rats during the cold exposure. Spatial learning (acquisition phase) and memory (probe trial) were tested in the Morris water maze immediately after daily exposure. Latency to locate the hidden platform, distance moved, mean distance to platform, swim speed and time spent in the platform quadrant were compared between genders and treatments. Field potential recordings were made, under urethane anesthesia, from the DG granule-cell layer, with stimulation of the medial perforant pathway 2 hours after the probe trial. This study examined spatial memory as measured by Morris Water Maze (MWM) performance and hippocampal long-term potentiation (LTP) in the dentate gyrus after exposure to cold in a repeated stress condition for 2 h/day for 5 days. Results: The cold-exposed female rats needed less time to find the hidden platform on day 1 (43.0±13.9 vs 63.2±13.2 sec), day 2 (18.2±8.4 sec vs 40.9±12.2 sec) and on day 4 (8.0±2.1 sec vs 17.2±7.0 sec) while cold-exposed male rats showed a decreased escape latency on day 1 only (37.3±12.5 sec vs 75.4±13.1 sec). Cold-exposed male rats spent less time in the target quadrant (30.08±6.11%) than the control male rats (37.33±8.89%). Two hour cold exposure decreased population spike potentiation during both induction (218.3±21.6 vs 304.5±18.8%) and maintenance intervals (193.9±